Pengembangan Sistem Booking Lapangan Berbasis Web untuk Meningkatkan Efisiensi Layanan di Solo Technopark - Melianingsih, Nuning; Harjono, Harjono; Nurhidayat, Taufik; Setyanavanny, Thessalonika Kris (Nusantara Journal of Education and Social Science, 2026)
The development of information technology encourages public service institutions to adopt digital systems to increase the quality of efficiency and service. Solo Technopark, as a center for developing of technology and entrepreneurship, has field facilities utilized by various parties. However, the field booking process is still done manually, so it potentially leads inefficiency, recording errors, and limited access in information. This study aims to develop a web-based field booking system that can simplify the booking process, schedule management, and present information in real-time. This website was created using observation and interview research methods. The system approach chosen is MDLC (Multimedia Development Life Cycle) with the stages of needs analysis, design, implementation, and testing. The system built provides online booking features, field schedules management, and facility usage reports. The field booking website was created using Laravel 8, the Tailwind CSS framework, and a MySQL database. The test results show that the system can run well using black box testing and is able to increase the service efficiency, reduce administrative errors, and increase user satisfactions, which was tested on 15 respondents. Therefore, this web-based field booking system is expected to be an effective digital solution in supporting the optimization of facility services at Solo Technopark.